If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4t + -7 = -15 Reorder the terms: -7 + 4t = -15 Solving -7 + 4t = -15 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 4t = -15 + 7 Combine like terms: -7 + 7 = 0 0 + 4t = -15 + 7 4t = -15 + 7 Combine like terms: -15 + 7 = -8 4t = -8 Divide each side by '4'. t = -2 Simplifying t = -2
| -13m=-78 | | 5x+3y-9=56 | | 22-3x-2=6x-5x | | -6(4q^2-4q+5)+5(-q^2+6q-3)= | | 32=2(3.14)r | | Qt+2x=c | | 5x^2+3x-9=36 | | 9x^5+18x^2+3x= | | .75(x-4)=1 | | 25x+20= | | -14x-7x+1=-7x+1 | | -15d+20d+-6=9 | | (7s+4)(7s-4)= | | 4(n+7)=3n | | 3b=7v+5 | | 2(6-6)+x=12+4x | | 7p-1=(p-2)+13 | | -8-3x=4-x | | 2x+9+3x-2=16 | | 1/5=1/5n-n-5/n | | 45h-1200=60k-1800 | | 5x-4+1=-18 | | -8-7x=-4+x | | 2x+9+3x-z=16 | | 15v-13v=20 | | 2(4x-3)-8=4+-2x | | (8x^3-2x^2+6x)-(3x^2+4x+5)= | | 2-4(x+5)=6x-8 | | y-x^2=-9 | | X-4=-7x-8 | | 5x+9y+3=0 | | 9+16s-7=7s+41-4s |